2005
DOI: 10.1007/s00411-005-0272-0
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetic modeling of uranium in man after injection and ingestion

Abstract: Uranium is a naturally occurring primordial radioactive element. Small amounts found in air, water, and food are regularly consumed and inhaled by humans. Even the military, medical, and industrial use of depleted uranium can affect humans. There is an appreciable retention of incorporated uranium in skeleton, kidneys, and liver, and a review of respective effective dose coefficients has been given by the International Commission on Radiological Protection (ICRP) in its "Publication 69"; however, data regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…For all three bodily fluids, the highest mean values were found in persons from the Halle region (Dobler et al, 2007a). For most of the world population the mean concentration in urine is about 10.0 ng U/L (Li et al, 2005). For Germany the mean uranium concentration in urine is 8.71 ng/L (Dobler et al, 2007a).…”
Section: Human Exposure To Uraniummentioning
confidence: 98%
“…For all three bodily fluids, the highest mean values were found in persons from the Halle region (Dobler et al, 2007a). For most of the world population the mean concentration in urine is about 10.0 ng U/L (Li et al, 2005). For Germany the mean uranium concentration in urine is 8.71 ng/L (Dobler et al, 2007a).…”
Section: Human Exposure To Uraniummentioning
confidence: 98%
“…Studies done in vitro showed that dieldrin binds to estrogen receptors (Soto et al, 1995), but no estrogenic effect was noted in a study that used cultured cells (Tully et al, 2000). Epidemiologic and animal studies have not conclusively associated dieldrin exposure with risk for developing Parkinson's disease (Corrigan et al, 2000;Kanthasamy et al, 2005;Li et al, 2005).…”
Section: Serum Aldrin (Lipid Adjusted)mentioning
confidence: 99%
“…In cases of retained DU shrapnel, the shrapnel acts as a source of chronic, low level exposure. After long term or repeated exposure, kidneys, liver, and bones can accumulate uranium with the largest amounts being stored in bones (Li et al, 2005). Uranium is eliminated in feces and urine; about 50% of the absorbed dose is eliminated in the urine within the first 24 hours.…”
Section: Urinary Uraniummentioning
confidence: 99%
“…The ICRP has developed comprehensive biokinetic models for radionuclides for more than two decades (ICRP, 1979). The systemic biokinetic models of uranium (ICRP, 1995a), coupled with the GIT model of ICRP Publication 30 (ICRP, 1979), the new HATM (ICRP, 2006) and the human respiratory tract model (HRTM) of ICRP Publication 66 (ICRP, 1994a), were used to model the excretion and the retention of 234 U, 235 U, 236 U and 238 U in organs or tissues after incorporation (Li et al, 2005).…”
Section: Biokinetic Model Of Uraniummentioning
confidence: 99%